Understanding the importance of Nutrition Tagsbetween Health Related & Non-Health Related Professionals - Madiha Ajaz, Sadia Sundus, Misbah Ajaz, Tooba Mehfooz, Sanowber Ajaz, Asma Aijaz (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To assess and compare understanding of nutritional tagsbetweenhealth related and non-health related professionals. Study design: cross sectional study Place of study: Rana LiaquatAli Khan College 1-10-2019 to 1-3-2020 Methodology: In this research questionnaire was used for data collection from 400 respondents by simple random sampling technique. Subjects involved in the study were health related and non-health related professionals, age ≥18, both male and female, middle and high income individuals, and healthy individuals and individuals with chronic disease. For assessing understanding of nutritional tags.Data was entered in SPSS version 20 and analyzed through using chi square test for independences. Results: Results (p value ˃0.05) shows that insignificant variance in understanding of nutritional tags among heath related and non-health related professionals. Conclusion: The research concluded that there is difference between understanding of nutritional labels in related and non-health related professionals. Further research is needed for better outcomes.